(untitled) - CORNEJO Y ROSADO, MIGUEL ANGEL (Mexico, 1994)
1.Excelencia humana / 2.El ser excelente / 3.Exito y fracaso / 4.
Keywords: 1.EXITO \ 2.CAMBIO ORGANIZACIONAL \ 3.MOTIVACION DEL EMPLEADO \ 4.LIDERAZGO